Guidelines for electrical transmission line structural loading - Agnew, Frank (American Society of Civil Engineers, 2020)
Prepared by the Task Committee on Electrical Transmission Line Structural Loading of the Electrical Transmission Structures Committee of the Special Design Issues Technical Administrative Committee of the Structural Engineering Institute of ASCEFully revised and updated, Guidelines for Electrical Transmission Line Structural Loading, Fourth Edition, MOP 74, provides the most current and relevant loading concepts and applications specific to transmission line design. A valuable resource for the development of a loading philosophy for electrical transmission structures, the information presented can be applied to an individual project or at a regional level. Key topics addressed in this manual areUniform procedures and definitions used in the industry for the calculation of loads,Design procedures addressing uniform levels of reliability for transmission lines,Up-to-date techniques for quantifying weather-related loads,Procedures for calculating design loads and determining their corresponding load factors, Updated techniques for quantifying wire system and other non-weather-related loads,Failure containment philosophy,andPractical examples providing more detail on the application of load recommendations. This Manual of Practice will be an important guide to engineers involved in electrical utility and structural engineering.
Keywords: Electric lines.; Load factor design -- Poles and towers -- Design and construction.; elektronické knihy; electronic books